Risk-communication issues in radiation safety: Mass consciousness about radiation and nuclear industry based on the results of a sociological research in St. Petersburg, the Leningrad region and the Murmansk region - N. V. Sokolov; A. M. Biblin; L. V. Repin; L. S. Rekhtina (Радиационная гигиена)
The study is devoted to a mass reflection of the problems of radiation safety and the functioning of the nuclear industry in the modern Russia. The analysis of the population’s awareness, peculiarities of the perception of radiation risks and the tendencies in the formation of a public assessment of large nuclear projects have been carried out. Materials and Methods: The data were collected during mass surveys of representative samples of the population of two regions located in the Northwest of the Russian Federation: 1) St. Petersburg and the Leningrad region. (2369 respondents, November 2016) and 2) the Murmansk region. (802 respondents May 2017). The results show that radiation is perceived by society as one of the most significant threats to life and health. However, the public concern does not give rise to a mass interest in the thematic information. The real level of knowledge of the population is clearly insufficient for literate actions in an extreme situation, or for the safe behavior in the everyday life. Public opinion is formed mainly on the basis of mass media reports. At the same time, it has been established that groups of the population well informed in the radiation field are much more likely, than others, to support the nuclear industry, including the least popular projects. Conclusion: Therefore, active informing of the population on the issues of the operation of nuclear facilities, the presence of radioactive contamination sites and other sources of danger, etc. objectively contribute to the growth of the industry’s reputation. It is advisable to use social technologies to overcome the cognitive and practical passivity of the Russian citizens and to form the population’s radiation culture.